2018
DOI: 10.1080/10872981.2018.1438719
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of implementing advanced access for residents in family medicine in Quebec. Do promising strategies exist?

Abstract: Background: The advanced access (AA) model is a highly recommended innovation to improve timely access to primary healthcare. Despite that many studies have shown positive impacts for healthcare professionals, and for patients, implementing this model in clinics with a teaching mission for family medicine residents poses specific challenges. Objective: To identify these challenges within these clinics, as well as potential strategies to address them. Design: The authors adopted a qualitative multiple case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Particular aspects of this study may limit the generalizability of findings. Firstly, it was conducted in teaching PHC clinics in Quebec that have certain characteristics – notably their teaching mission and the broad range of PHC providers working alongside physicians – that distinguish them from other clinical settings ( Abou Malham et al 2018 ). Secondly, the participating U-FMGs were located in both rural and urban areas, but information was not collected to enable analysis of the differences between these settings.…”
Section: Discussionmentioning
confidence: 99%
“…Particular aspects of this study may limit the generalizability of findings. Firstly, it was conducted in teaching PHC clinics in Quebec that have certain characteristics – notably their teaching mission and the broad range of PHC providers working alongside physicians – that distinguish them from other clinical settings ( Abou Malham et al 2018 ). Secondly, the participating U-FMGs were located in both rural and urban areas, but information was not collected to enable analysis of the differences between these settings.…”
Section: Discussionmentioning
confidence: 99%
“…This study is nested within a larger multiple case study conducted in four UFMGs in the province of Quebec [ 16 ] that are considered early adopters of AA. University Family medicine groups (UFMGs) are public primary healthcare organizations with a teaching mission, devoted to training family medicine residents [ 22 ], and enabling them to learn how to work as part of an inter-professional team including FPs, nurses, pharmacists and social workers. Selection of the four FMUs is based on two criteria: 1) having at least 1 year of experience in implementing AA; and 2) representing diverse socio-demographic environments (rural and urban UFMGs).…”
Section: Methodsmentioning
confidence: 99%
“…UFMGs are an exemplary setting that provides early exposure of future health professionals' to best practices during their training program and are potentially conducive to implementing advanced access in their future practice [23]. Aside from the exploratory study [24] that we conducted, few studies has been identified on the impact of variations in advanced access implementation in various teaching settings [25]. We observed different models of implementation of advanced access by residents, ranging from a simple pairing/ twinning (i.e., sharing a panel of patients between two residents) to the implementation of a joint care model with nurses or a subteam (teamlet) of professionals, in which the resident is included.…”
Section: Study Contextmentioning
confidence: 99%